Current and future treatments of pulmonary arterial hypertension. (23rd March 2020) - Sommer, Natascha; Ghofrani, Hossein A.; Pak, Oleg; Bonnet, Sebastien; Provencher, Steve; Sitbon, Olivier; Rosenkranz, Stephan; Hoeper, Marius M.; Kiely, David G.
Abstract : Therapeutic options for pulmonary arterial hypertension (PAH) have increased over the last decades. The advent of pharmacological therapies targeting the prostacyclin, endothelin, and NO pathways has significantly improved outcomes. However, for the vast majority of patients, PAH remains a life‐limiting illness with no prospect of cure. PAH is characterised by pulmonary vascular remodelling. Current research focusses on targeting the underlying pathways of aberrant proliferation, migration, and apoptosis. Despite success in preclinical models, using a plethora of novel approaches targeting cellular GPCRs, ion channels, metabolism, epigenetics, growth factor receptors, transcription factors, and inflammation, successful transfer to human disease with positive outcomes in clinical trials is limited. This review provides an overview of novel targets addressed by clinical trials and gives an outlook on novel preclinical perspectives in PAH. LINKED ARTICLES: This article is part of a themed issue on Risk factors, comorbidities, and comedications in cardioprotection. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.1/issuetoc